DEVELOPMENT OF GEOGRAPHICAL INFORMATION SYSTEM FOR WEST SUMATERA SOUVENIR TOURISM - Hadi syahputra; Novi Trisna; Dodi Guswandi (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2020)
West Sumatra is one of the tourist destinations in Indonesia. It is not only related to its history, but also holds anumber of tourism potentials from its alluring natural scenery, shopping tours, to culinary tours. West Sumatraoriginal souvenirs and souvenirs are an inseparable part of the experience while traveling. However, tourists stillfind it difficult to find a good outlet or shop, close to tourist sites, and find information related to souvenirs andsouvenirs in West Sumatra. For this reason, a GIS-based gift and souvenir travel application was built.Geographical Information System for souvenirs and souvenir tours was built in several stages, namely thesystem analysis stage, the system design stage, the implementation stage and the testing phase. The map designin the system uses the Google Maps API and the software used in building this application is the programminglanguage HP (Pear Hypertext Prepocessor), JavaScript, jQuery, XAMPP database and Adobe Dreamweaver.Presentation of information on the web includes information on tourism objects, culinary gifts and souvenirs orsouvenirs.